Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd000978.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing oral mucositis for patients with cancer receiving treatment

Abstract: BackgroundTreatment of cancer is increasingly more effective but is associated with short and long term side effects. Oral side effects remain a major source of illness despite the use of a variety of agents to prevent them. One of these side effects is oral mucositis (mouth ulcers). ObjectivesTo evaluate the effectiveness of prophylactic agents for oral mucositis in patients with cancer receiving treatment, compared with other potentially active interventions, placebo or no treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 280 publications
0
19
0
11
Order By: Relevance
“…46 Similarly, oral or intravenous glutamine can reduce the severity of mucositis, but clinical evidence for its efficacy in preventing infections is lacking. 47,48 Without any specific interventions, mucosal damage starts to heal just before, or with the recovery of granulocytes in peripheral blood (PB), 49 as neutrophil recruitment to the site of mucosal injury may occur up to a week before recovery of neutrophils in PB. 50,51 Reconstitution of the innate cellular immune system…”
Section: Recovery Of Mucosal Injurymentioning
confidence: 99%
“…46 Similarly, oral or intravenous glutamine can reduce the severity of mucositis, but clinical evidence for its efficacy in preventing infections is lacking. 47,48 Without any specific interventions, mucosal damage starts to heal just before, or with the recovery of granulocytes in peripheral blood (PB), 49 as neutrophil recruitment to the site of mucosal injury may occur up to a week before recovery of neutrophils in PB. 50,51 Reconstitution of the innate cellular immune system…”
Section: Recovery Of Mucosal Injurymentioning
confidence: 99%
“…73 A total of 131 studies with 10 514 randomised participants were included. Nine interventions, in which there was more than one trial in the meta-analysis, were found to have some benefit with regard to preventing or reducing the severity of mucositis associated with cancer treatment, and aloe vera was involved in one of them.…”
Section: Aloe Vera Anti-inflammatory and Gastrointestinal Actionsmentioning
confidence: 99%
“…(10) La mucositis es la reacción inflamatoria que tiene lugar en el epitelio de todo el tracto gastrointestinal, desde la boca hasta el ano, a consecuencia de los tratamientos antineoplásicos tales como la radioterapia, la quimioterapia o el trasplante de médula ósea, siendo muy frecuente en los tratamientos de los procesos oncohematológicos. (11) En la cavidad oral, con la presencia de mucositis, se ven reflejados, los cambios que ocurren en todo el recubrimiento mucoso. (6) Debemos destacar, que el paladar blando, la mucosa yugal, los labios y el piso de boca, son más vulnerables al daño tóxico directo por ser áreas de mucosa no queratinizada, si se compara con las encías, superficie dorsal de lengua y paladar duro.…”
Section: Mucositisunclassified
“…En conclusión, la crioterapia parece ser efectiva en la prevención de la mucositis inducida por quimioterapia y en concreto por los fármacos 5-FU, melfalán y edatrexato. (11)…”
Section: Modificadores De La Respuesta Biológicaunclassified
See 1 more Smart Citation